Exercise enhances motor skill learning by neurotransmitter switching in the adult midbrain - Li, Hui-quan (Nat Commun, 2020)
Physical exercise promotes motor skill learning in normal individuals and those with neurological disorders but its mechanism of action is unclear. We find that one week of voluntary wheel running enhances the acquisition of motor skills in normal adult mice. One week of running also induces switching from ACh to GABA expression in neurons in the caudal pedunculopontine nucleus (cPPN). Consistent with regulation of motor skills, we show that the switching neurons make projections to the substantia nigra (SN), ventral tegmental area (VTA) and ventrolateral-ventromedial nuclei of the thalamus (VL-VM). Use of viral vectors to override transmitter switching blocks the beneficial effect of running on motor skill learning. We suggest that neurotransmitter switching provides the basis by which sustained running benefits motor skill learning, presenting a target for clinical treatment of movement disorders.